A Case of Paroxysmal Nocturnal Hemoglobinuria (PNH) in an Obstetric Patient: A South African Perspective - Garrick Laudin (Clinical Management Issues, 2019)
Paroxysmal Nocturnal Hemoglobinuria (PNH) originates from an acquired genetic defect in a multipotent hematopoietic stem cell that becomes stem-cell-like in its ability to survive, expand, and self-renew. PNH is a rare condition characterized by intravascular hemolysis. PNH can arise anew or in the setting of an underlying bone marrow disorder such as aplastic anemia (AA), myelodysplastic syndrome (MDS), or primary myelofibrosis (PMF). This case presentation documents the challenging diagnosis of PNH in the obstetric setting, in which other possible causes for a hemolytic anemia could be considered. We discuss the management of a pregnancy in the presence of PNH in a low-to-middle income setting.